2008
DOI: 10.1149/1.2830850
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemistry of Porous p-Cu[sub 2]O Films

Abstract: Porous p-Cu 2 O films were prepared on transparent conductive glass from a dispersion of Cu 2 O powder in ethanol. Upon illumination with a 100 W tungsten lamp, the photocurrent of the porous Cu 2 O film was appreciably greater when compared to electrodeposited Cu 2 O films. The enhancement is attributed to the increased interfacial area between the film and the solution due to the three-dimensional nature of the Cu 2 O film. No chemical change was detected by visual examination and X-ray diffraction of the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 23 publications
3
54
0
1
Order By: Relevance
“…Some of us reported that the stability and reactivity of electrodeposited Cu 2 O films depends on the crystal orientation. 2 4 Our premise of a [111] oriented Cu 2 O film being predominately O 2− -terminated agrees with their finding. We have reasoned that the useful Cu 2 O surfaces for photo-assisted H 2 production are the ones terminated with O 2− , which attract H + , however, it is necessary to interrupt the direct interaction of O 2− -terminated surface with H + to prevent the decomposition reaction.…”
supporting
confidence: 89%
“…Some of us reported that the stability and reactivity of electrodeposited Cu 2 O films depends on the crystal orientation. 2 4 Our premise of a [111] oriented Cu 2 O film being predominately O 2− -terminated agrees with their finding. We have reasoned that the useful Cu 2 O surfaces for photo-assisted H 2 production are the ones terminated with O 2− , which attract H + , however, it is necessary to interrupt the direct interaction of O 2− -terminated surface with H + to prevent the decomposition reaction.…”
supporting
confidence: 89%
“…In this study, we demonstrate that the same solution can be successfully explored for the formation of densely packed pyramidal-and bi-pyramidal-shaped (octahedral) Cu 2 O crystals onto the thermally oxidized Ti substrate ( Figures 1C and D). The shape of crystallites was found to be dependent on the pH of solution and AC deposition conditions, similar to the case of potentiostatic depositions from the alkaline cupric lactate solution onto the ITO substrate [27]. The pH of solution kept at a pH within 5.2 to 5.35 range was found to be an optimal.…”
Section: Composition and Structure Of Heterostructured Filmssupporting
confidence: 59%
“…Among the abundant semiconductors, cuprous oxide (Cu 2 O) has recently attracted extensive attention as a means of solar-to-hydrogen conversion [4][5][6]. In addition to possessing low cost and environmental friendliness, the fascination also comes from its peculiar conduction band lying 0.7 V negative of the hydrogen evolution potential [4,7], which theoretically points out its feasibility to drive the water splitting into hydrogen. In addition, the high theoretical photocurrent of À 14.7 mA cm À 2 and light-to-hydrogen conversion efficiency of 18.7% suggest its huge potential applications in solar hydrogen production [8].…”
Section: Introductionmentioning
confidence: 99%